PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTU MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SDN KALICARI 02 SEMARANG - Nanda Aprilia Sedyaningtyas; Khusnul Fajriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of the PBL model assisted by mind mapping on students' critical thinking skills. The background of this study is the low critical thinking skills of fourth grade students of SDN Kalicari 02 Semarang. This is because students' ability to remember material is very low. There are still students who cannot conclude the contents of the learning in class and the learning model has not been used by the teacher when teaching. This study uses quantitative research in the form of Pre Experimental Design with One Group Pretest-Posttest Design. The population in this study were all fourth grade students of SDN Kalicari 02 Semarang in the 2024/2025 academic year. The sample used in this study was 27 students with a saturated sampling technique. The data in this study were obtained through observation, interviews, and tests. Then the data analysis used the normality test and the t-test (paired sample t-test). The results showed that the average pretest score was 50.93 and the average posttest score was 83.52. The results of the data above show that the average posttest score is higher than the pretest score. This is also proven by the results of the t-test hypothesis test obtained a Sig. (2-tailed) value of <0.000 <0.05, meaning that the significance value in the pretest and posttest is less than 0.05. So H0 is rejected and Ha is accepted. So it can be concluded that there is a significant influence of the PBL model assisted by mind mapping on the critical thinking skills of grade IV students of SDN Kalicari 02 Semarang.